EVALUATIONOF GROWTH, YIELD, NUTRITIVE VALUE ANDCOSTOFPRODUCTIONOFMAIZE FODDER GROWN UNDER HYDROPONIC SYSTEMS - G. Rajkumar; M.T. Dipu; P. Gangadevi; K. Lalu; K. Shyama; K.S. Anil (Journal of Veterinary and Animal Sciences, 2017)
The present study aimed to evaluate the growth, yield, nutritive value and cost of production of maize fodder under hydroponic system. Maize fodder was produced in nine days from planting to harvest by hydroponic technique . Shoot and root length of hydroponic fodder maize were meausred during successive days of growth and on the ninth day of cultivation shoot and root length were 26 cm and 19.60 cm respectively. The yield of maize fodder per kg seed recorded on the ninth day of cultivation was 4.72 kg. Dry matter, crude protein, ether extract, crude fiber, NFE, total ash and acid insoluble ash levels were 17.26, 13.01, 3.47, 8.72, 71.89, 2.95 and 0.53 per cent, respectively on ninth day of cultivation. The crude protein, ether extract, total ash and acid insoluble ash contents of hydroponic maize fodder was higher (P<0.05) than maize seed. The cost of production per kg of hydroponic maize fodder was Rs.5.26.